100 deadly skills survival edition : the SEAL operative's guide to surviving in the wild and being prepared for any disaster - Emerson, Clint; Slampyak, Ted (New York Touchstone, 2016)
"These 100 skills, adapted for civilians from actual field experiences of special forces operations, offer a complete hands-on and practical guide to help you survive in the wild no matter the climate or terrain; be prepared for any crisis; and have the critical life-saving knowledge for staying safe in any hostile environment or disaster."
Personal Preparedness -- Navigation -- Survival In The Wild -- Defending Your Domain -- Securing Public Spaces -- Neutralizing Public Safety Threats -- Disaster Survival -- Signaling For Help -- Emergency Medicine.
Includes index.
Keywords: United States. -- Navy. -- SEALs; Combat survival -- Handbooks, manuals, etc; Survival -- Handbooks, manuals, etc